An unusual giant serpiginous lesion of secondary syphilis - Xavier Grimaux; Rida El Ayoubi; Christian Le Clec'h (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Syphilis is a worldwide sexually transmitted infection caused by Treponema pallidum subspecies pallidum. Its association with other STIs, including HIV, demands early diagnosis and immediate treatment of patients. We herein report an unusual serpiginous form of secondary syphilis.